Perancangan Aplikasi Prototyping API Web dalam Menyimpan Data Pergerakan Cryptocurrency Menggunakan CURL - Rizky Parlika; Rifky Akhmad Fernanda; Melinda Shilatil Fauziyah; Nafa Nabila El Indri (Teknik Informatika Universitas Pamulang, 2022)
Virtual currency technology is developing in various countries. Cryptocurrencies are used for the purposes of buying, trading and investing. Cryptocurrency marketplace Rekeningku.com provides API (Application Programming Interface) services that can be accessed by third parties that can be used in making applications to make it easier to monitor price movements of several coins. Utilization of URL service (Uniform Resource Locator) API Rekeningku.com in the form of JSON data (JavaScript Object Notation) is used to monitor and store data into the database to make predictions and analyze the movement of certain patterns. The coin movement monitoring application uses the SDLC (Systems development life cycle) prototyping method to develop applications quickly. API calls use the structure of how to get data in the form of endpoint prices to display a list of markets and their assets. The website application in its application uses a web browser application service based on the PHP (Hypertext Preprocessor) and Javascript programming languages. Utilization of the PHP CURL library (Client URL) is used to process API data. The point of research’s results are in the form of a website-based application model and database integration in storing data on coin asset movements in all marketplaces. Applications can be applied in general within the scope of Rekeningku.com service.